O psychologicznych podstawach uczenia się i nauczania systemowego = Psychological bases of learning and system teaching - Jerzak, Józef (1931-2017) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The term "system teaching" is used in this paper according to E. Fleming and W. Pasterniak. The author divides the systems into l. definite - workable, 2. national verbal and 3. theoretical abstract. The author also discusses the problem of systematization of knowledge according to psychology taking into account the effect law and the possibility of alternative choice of information.
Keywords: Uczenie się - metody; nauczanie systemowe; psychologia